ANALISIS KINERJA KEUANGAN BANK MUAMALAT INDONESIA DENGAN MENGGUNAKAN PENDEKATAN LABA RUGI DAN NILAI TAMBAH (Survei Pada PT Bank Muamalat Indonesia) - Putri - Kartika P; Djoko - Kristianto (Universitas Slamet Riyadi, 2013)
ABSTRACT The limitations of SFAS 59, the accounting standard guidelines for Islamic banks do not comply with the principle of full disclosure, led to the information presented in the financial statements are not accurate, especially with regard to the ability of Islamic banks to generate profits. The purpose of this study, to analyze the differences in the financial performance of Islamic banks using the income approach and the value -added based on financial ratios. The results showed that by using a value-added approach, the ratio of financial performance (ROA, ROE, and the ratio of total income to total earning assets) there are differences in quantitative, value-added approach is greater than the income approach. Keywords: Financial Performance, Islamic Banking, Income Statement, Statement of Value Added